ANALISIS CLUSTERING STUNTING DENGAN DISTANCE EUCLID - Buaton, Realita (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2024)
Entering the Industrial Revolution Era 4.0, human resources must be supported by healthy and intelligent human resources so that they can increase competitiveness. The world still faces the problem of hunger and malnutrition today. According to a Unicef report, many people suffer from malnutrition in the world. The World Health Organization (WHO) says that malnutrition is a dangerous threat to the health of the world's population. Stunting also has an impact in Indonesia, the prevalence of toddlers experiencing stunting in Indonesia is 24.4% in 2021. The solution created is to classify and cluster stunting so as to produce patterns that can be used as best practice to be transmitted to other affected areas. The algorithm used is Euclid, the Euclid algorithm is able to cluster stunting prevalence data into 3 clusters with a little category of 66%, a medium category of 28%, a lot of category of 6%. The results of the classification and clustering of the best stunting prevalence in cluster two with a small number, can be used as a source of accurate and updated information that can be used by the government in its efforts to optimize stunting handling in each district/city based on artificial intelligence which can provide patterns for handling and optimizing stunting. in each district/city. Malnutrition is estimated to be the main cause of 3.1 million child deaths every year. Therefore, efforts need to be made to minimize stunting by predicting stunting sufferers. The prediction results can be used as an early prevention effort.